Health care response to the tsunami in Taro District, Miyako, Iwate Prefecture - Kuroda, Hitoshi (Western Pacific Surveillance and Response, 2013)
Problem: In the Taro District (population: 4434), the great tsunami of 11 March 2011 destroyed the central region including the clinic, the sole medical facility (one physician, 13 nurses and other staff) in the district, and many citizens were forced to live in evacuation centres.Context: The Taro District experienced massive damage during the tsunamis of 1896 and 1933. Since then countermeasures to tsunamis have been implemented. The great tsunami on 11 March 2011 caused catastrophic damage to the low-lying areas where approximately 2500 people lived; 1609 buildings were completely destroyed, and approximately 200 people died or were missing across the district.Action: The Taro National Health Insurance Clinic, the sole medical facility in the Taro District, was required to play a central role in a variety of activities to care for residents in severely affected areas. First of all, evacuees needed to move to neighbouring hospitals or safer evacuation centres because lifeline services were cut off to the first evacuation centre. Then, the clinic staff worked in a temporary clinic; they visited the evacuation centres to assess the public health and medical situation, cared for wounded residents, managed infection control and encouraged a normal lifestyle where possible. Additional medical, pharmaceutical and logistical support was received from outside the district.Outcome: There was no noticeably severe damage to health, although there was manifestation of and deterioration in lifestyle-related diseases (e.g. diabetes, hypertension, obesity). Health care activities gradually returned to their pre-disaster levels. At the end of July 2011, the evacuation centres closed, and all evacuees moved to temporary accommodations.Discussion: Isolated rural health practitioners were required to be involved in a wide variety of activities related to the disaster in addition to their routine work: e.g. preventive health (public health and safety activities), routine medical care, acute medical care, psychological care, post-mortems and recovery of medical facilities. Although the whole health care system returned to near-normal six months after the disaster, it is important to plan how to develop more resilient medical systems to respond to disasters, especially in rural areas. This article describes my experience and lessons learnt in responding to this disaster.